2021
DOI: 10.1038/s41598-021-84880-9
|View full text |Cite
|
Sign up to set email alerts
|

Pictures of social interaction prompt a sustained increase of the smile expression and induce sociability

Abstract: Viewing pictures of social interaction can facilitate approach behaviors. We conducted two studies to investigate if social interaction cues, empathy, and/or social touch modulate facial electromyographic (EMG) reactivity (as evidenced by the zygomaticus major and corrugator supercilii muscles) and mood states. We presented bonding pictures (depicting social interaction) and control pictures (without social interaction) while continuously recording zygomatic and corrugator EMG activities. In both studies, pict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 36 publications
(30 reference statements)
2
7
0
Order By: Relevance
“…Therefore, in the non-depressive group, the affiliative pictures motivated social interactions, increasing states of sociability (reducing the fear of rejection scores), an effect not observed in the depressive group. These results corroborate those described in the literature, which showed a reduced fear of rejection after viewing affiliative pictures in non-depressive individuals 9 , 23 . It is known that people with depression often have the expectation that they might be rejected or that it is too exhausting to engage with others 48 , 49 , which may also lead to less mimicry behavior and less states of sociability.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Therefore, in the non-depressive group, the affiliative pictures motivated social interactions, increasing states of sociability (reducing the fear of rejection scores), an effect not observed in the depressive group. These results corroborate those described in the literature, which showed a reduced fear of rejection after viewing affiliative pictures in non-depressive individuals 9 , 23 . It is known that people with depression often have the expectation that they might be rejected or that it is too exhausting to engage with others 48 , 49 , which may also lead to less mimicry behavior and less states of sociability.…”
Section: Discussionsupporting
confidence: 92%
“…Higher valence stimuli increase the EMG activity of the zygomatic major muscle, while lower valence stimuli show lower activation of this musculature 7 , 19 . The results observed in non-depressive individuals corroborate those reported previously and are consistent with those of a study showing increased zygomatic activity for social interaction pictures (preceded or not by a priming text) compared to control pictures also pared by valence and arousal 9 . Additionally, the temporal analysis during image visualization showed that the affiliative pictures promoted increased smile expression from 0.5 s onwards compared to the control pictures, a difference that persisted until the end of the image visualization.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Of importance for the current discussion, a previous study showed that visual social stimuli promoted an accelerated reaction time in the flexion of the fingers, a motor task that bears resemblance with the social touch (Souza et al, 2012 ). Additionally, it was found that exposure to bonding pictures (with social touch cues) increased subjective feelings of sociability and activity of smile muscles (Mota et al, 2021 ) as well as the activity of muscles involved in a caress-like movement (Campagnoli et al, 2015 ). Furthermore, the authors provided evidence of decreased feelings of isolation after priming with bonding pictures and a reduction in the motor readiness potential amplitude preceding caress on a soft cloth (Campagnoli et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%